Burnout in customer service representatives - Tariq Jalees; Javed Zeeshan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
The purpose and aim of this research was to (1) identify the factors that contributes towards job burnout in sales service representative (2) What are the relationships of these factors (3) To empirically test the relationships of the determinants relating to burnout in customer service representatives. Based on literature survey six different variables related to burnout were identified. The variables were (1) Emotional exhaustion.(2) Reduced personal accomplishment.(3) Job induced tension.(4) Job satisfaction.(5) Workload (6) Job satisfaction. Each of the variables contained 3 sub-variables. Five different hypotheses were developed and tested through techniques such as Z-test, F-test and regression analysis. The questionnaire administered for the study contained 15 questions including personal data. The subject was Moblink company customers sales service representative in Karachi.The valid sample size was 98 drawn through multi-cluster technique. Techniques such as measure of dispersion and measure of central tendencies were used for analyzing the data. Regression, Z-test, and F-test were used for testing the developed hypothesis. According to the respondents' opinions, the reduced personal accomplishment had a high rating with a mean of 3.75 and job induced tension has the lowest mean of 3.58. The standard deviation of respondents' opinions was highest for dimension depersonalization and least for dimension work load. This indicates that there is a high polarization of the respondents' opinions on the dimension depersonalization moral and least on the dimension work load. The Skew nesses for all the dimensions were in negative except the determinants emotional exhaustion and workload. This indicates that the majority of respondents' opinions on all the dimensions were below the mean except in the case of emotional exhaustion and workload. Five hypotheses were developed and tested: a) The hypothesis relating to low level of burnout in customers service representative was rejected. b) The hypothesis relating to no significant difference in the burnout levels of younger age group and older age group was accepted. c) The hypothesis relating to higher level of burnout in the single customers sales representatives as compared to married ones was accepted. d) Alternative hypothesis of relationship between independent variable "Job satisfaction" and dependent variable "Burnout" was accepted. e) Alternative hypothesis of relationship between independent variable "Work load" and dependent variable "Burnout" was accepted.
Keywords: 330